Asthmatics with high levels of serum surfactant protein D have more severe disease. Issue 6 (17th March 2016) - Benfante, Alida; Battaglia, Salvatore; Principe, Stefania; Di Mitri, Chiara; Paternò, Alessandra; Spatafora, Mario; Scichilone, Nicola
Pulmonary surfactant is a mixture of lipids and surfactant-specific proteins that covers the alveolar surface, as well as the terminal conducting airways, lowering the surface tension at the air–liquid interface during breathing. The involvement of pulmonary surfactant in the pathophysiology of asthma has been suggested [1–4]. An interesting working hypothesis is that the surface tension of the peripheral airways is altered in asthma, because the inflammatory process affects the structure and function of surfactant, leading to excessive airway narrowing and features of air trapping. We explored whether serum levels of surfactant protein D (SP-D) in asthmatics are related to the severity of the disease. In addition, we aimed to assess whether serum SP-D correlated with functional abnormalities of peripheral airways. Serum surfactant protein D could serve as a biomarker of small airways damage and severity of asthma http://ow.ly/YdeG9